TINGKAT KEPUASAN KONSUMEN DI RUMAH KOPI K8 DI KOTA MANADO - Yeremia Gerry Putra Mongan; Grace A.J. Rumagit; Ribka M. Kumaat (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
The purpose of this study was to know the level of customer satisfaction in the K8 Coffee House. Survey Method was used in this study. The data used were primary data collected using interview techniques in the form of questionnaires.The level of customer satisfaction in K8 coffee house was determined by total score in each criterion.The research result showed that the score reached 6659 and the number of satisfaction index was 78.11% which could be classified as satisfied.Â  Keywords: satisfaction, customers, coffee house, Manado City.